2020
DOI: 10.1093/hmg/ddaa008
|View full text |Cite
|
Sign up to set email alerts
|

Retinal degeneration in mice expressing the constitutively active G90D rhodopsin mutant

Abstract: Rhodopsin is the G protein-coupled receptor in rod photoreceptor cells that initiates vision upon photon capture. The light receptor is normally locked in an inactive state in the dark by the covalently bound inverse agonist 11-cis retinal. Mutations can render the receptor active even in the absence of light. This constitutive activity can desensitize rod photoreceptor cells and lead to night blindness. A G90D mutation in rhodopsin causes the receptor to be constitutively active and leads to congenital statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Some of these are thought to cause only rod dysfunction (CSNB) (e.g., G90D, T94I, A292E, A295V) [ 1 , 2 , 4 , 9 , 10 , 18 , 19 ], while others were associated with retinal degeneration (RP) (e.g., G90V, S186W, D190N, K296E, K296M) [ 1 , 2 , 3 , 4 , 5 , 6 , 20 ]. The p.G90D mutation is located in the middle of the second transmembrane domain [ 21 ] and is thought to results in constitutive activity of the photoreceptor [ 1 , 3 , 6 , 9 , 12 ]. Biochemical studies have shown a blue-shifted absorbance maximum of G90D rhodopsin and a change in hydroxylamine accessibility, indirectly suggesting structural alterations in dark state rhodopsin that usually occur in light-activated wild-type rhodopsin [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of these are thought to cause only rod dysfunction (CSNB) (e.g., G90D, T94I, A292E, A295V) [ 1 , 2 , 4 , 9 , 10 , 18 , 19 ], while others were associated with retinal degeneration (RP) (e.g., G90V, S186W, D190N, K296E, K296M) [ 1 , 2 , 3 , 4 , 5 , 6 , 20 ]. The p.G90D mutation is located in the middle of the second transmembrane domain [ 21 ] and is thought to results in constitutive activity of the photoreceptor [ 1 , 3 , 6 , 9 , 12 ]. Biochemical studies have shown a blue-shifted absorbance maximum of G90D rhodopsin and a change in hydroxylamine accessibility, indirectly suggesting structural alterations in dark state rhodopsin that usually occur in light-activated wild-type rhodopsin [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Around 200 mutations in the rhodopsin gene ( RHO ) cause retinal diseases, in most patients in the form of retinitis pigmentosa (RP) [ 2 , 3 , 4 , 5 ], although other phenotypes have also been described, including sector RP [ 6 ], pericentral RP [ 7 ], congenital stationary night blindness (CSNB) [ 1 , 2 , 3 , 4 , 5 ], and retinitis punctata albescens [ 8 ]. Some of these pathogenic variants are thought to cause the photoreceptor to be constitutively active (activity in the absence of light) based on their conformational changes and the accessibility of the chromophore-binding pocket [ 3 , 9 , 10 , 11 ]. Constitutively active mutants have been associated with both RP and CSNB phenotypes [ 3 , 9 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations